Physiology and biophysics of plant ligand-gated ion channels. - Dietrich, Petra; Anschuetz, U.; Kugler, Annette; Becker, Dirk (Botanica Acta, 2010)
Small molecules and metabolites often act as intra- or extracellular messengers in signal transduction pathways. Ligand-gated ion channels provide a mean to transduce those biochemical signals at the membrane into electrical events and ion fluxes. In plants, cyclic nucleotides and glutamate represent intra- and extracellular signalling ligands, respectively. While the former have been shown to regulate voltage-dependent ion channels and are supposed to activate cyclic nucleotide gated (CNG) channels, the latter are perceived by ionotropic glutamate receptors (GLRs). This review summarises our current knowledge about CNG channels and glutamate receptors in plants and their proposed roles in plant development and adaptation to biotic and abiotic stresses.